2020
DOI: 10.5650/jos.ess20128
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Physical Characterization of the Hackberry (<i>Celtis australis</i>) Seed Oil: Analysis of Tocopherols, Sterols, ECN and Fatty Acid Methyl Esters

Abstract: IntroductionRecently, due to the increasing demand for fast foods and fatty diets in modern countries, it has become important to explore more nutritional and unsaturated edible oils from natural resources. Exploring and finding the edible oils containing high polyphenols, natural antioxidants, omega 3, 6 & 9, with less saturated fatty acid, are worth to health care. These needs have driven the governments to intensify their efforts in evaluating the nutritional values of available plants and the natural fortu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Regarding antimicrobial potential of C. australis, several studies demonstrated that various hackberry extracts, prepared with different solvents, may act as antibacterial agents (Ahmad et al, 2012;Alonso-Esteban et al, 2018;Nodeh et al, 2020;Ota et al, 2017;Zehrmann et al, 2010). Nevertheless, antifungal properties of C. australis extracts were poorly investigated (Alonso-Esteban et al, 2018;Nodeh et al, 2020;Ota et al, 2017). Ota et al (2017) against biotic and abiotic stress, particularly against phytopathogenic fungi (Lattanzio et al, 2006;Vagiri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding antimicrobial potential of C. australis, several studies demonstrated that various hackberry extracts, prepared with different solvents, may act as antibacterial agents (Ahmad et al, 2012;Alonso-Esteban et al, 2018;Nodeh et al, 2020;Ota et al, 2017;Zehrmann et al, 2010). Nevertheless, antifungal properties of C. australis extracts were poorly investigated (Alonso-Esteban et al, 2018;Nodeh et al, 2020;Ota et al, 2017). Ota et al (2017) against biotic and abiotic stress, particularly against phytopathogenic fungi (Lattanzio et al, 2006;Vagiri et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, ripe fruits have high content of sugars, proteins, crude fibers, oils, ash, and minerals (Demir et al, 2002 ). A significant quantity of lipophilic compounds were also determined in fruits of wild‐growing C. australis from Iran, such as linoleic acid, γ ‐tocopherol (87%), and β ‐sitosterol (Nodeh et al, 2020 ). According to Badoni et al ( 2010 ), ripe fruits are rich in celtisanin (sulfonated phenolic compound) along with several fatty acids, methyl oleate, and methyl palmitate as the main compounds.…”
Section: Introductionmentioning
confidence: 99%